Survey on Management of White Spot Lesions - N.E.Kaviya1 , S.Haripriya2 , Anitha Roy3 (Indian Journal of Forensic Medicine & Toxicology, 2020)
White spot lesion occurs due to the demineralization of enamel.The white spot lesion is also caused byhypomineralization, fluorosis etc. It can be identified by visual as well as radiographic methods. The whitespot lesion can mainly be prevented by maintaining proper oral hygiene. Other methods of management ofwhite spot lesions include fluoride therapy, calcium phosphate, resin infiltration and CPP-ACP. The usageof remineralizing agents also helps in preventing and treating white spot lesions. This survey was conductedwith a questionnaire about the management of white spot lesion and was circulated among 100 specialistsand general practitioners. Data collection was done and analysed. The graphs were plotted according tothe responses obtained from the survey. The results of the survey showed that the participants prefered theproper maintenance of the oral hygiene to prevent the white spot lesion. In case of no proper oral hygienethe participants preferred the usage of different techniques available to revert demineralisation. There wasno significant association between the field of practice (specialist /general practitioners) and their responseto the question. The participants had a good knowledge regarding the management of the white spot lesionand most of them were aware regarding the different modalities of treatment available and implied them intheir clinical practice.